Pengaruh Gaya Hidup, Kepribadian dan Kewajaran Harga Terhadap Keputusan Pembelian pada Toko Hijab Ummi Collection - Saputri Cita Nurahmasari; Sigit Wibawanto (Jurnal Ilmiah Mahasiswa Manajemen, Bisnis dan Akuntansi, 2021)
This study aims to examine and analyze the effect of lifestyle, personality, and price fairness on purchasing decisions. This research was conducted on consumers who are in the gombong area and who have made purchases at the Ummi Collection hijab store. Data collection was carried out through distributing questionnaires to 100 respondents who were in the gombong area and who had made purchases at the Ummi Collection hijab store. Data collection techniques by distributing questionnaires. The analysis used is validity test, reliability test, classical assumption test, multiple linear analysis test and coefficient of determination. The analysis technique used is the SPSS Analysis version 23 for Windows program. The results obtained in the study indicate that the variables of lifestyle, personality, and fairness of price have a significant effect on purchasing decisions. Lifestyle variables have a significant effect on purchasing decisions, personality variables have a significant effect on purchasing decisions, while the price fairness variable has no significant effect on purchasing decisions.